EVALUASI ADOPSI AGILE SOFTWARE DEVELOPMENT METHODOLOGYSTUDI KASUS: PEMBANGUNAN APLIKASI DANA OTSUS - Muhammad M Hakim; Suryarini Widodo (INTECOMS: Journal of Information Technology and Computer Science, 2026)
Up until 2022, all application developments in Directorate ABC are still using waterfall method. There are several applications from it that cannot be used anymore because their user requirement does not imply to existing policies dan government rules. In order to make application development more comply to the updated business process, according to Directorate ABC information system development guideline, user must submit new UR that suitable for it. That makes tardy applications availability, because it must follow all the steps in order to develop application using waterfall. In early 2023, there was a plan to develop special autonomy fund application. Reflecting on previous experiences that waterfall-based applications are quite unuseful, application development team decided to use more flexible and agile methods. This research aims to assess how useful Extreme Programming Method implementation in developing special autonomy funds applications and to measure successful rate by using EUCS instrument. Keywords: Agile, Dana Otsus, EUCS, Extreme Programming